The Library of the Sidneys of Penshurst Place circa 1665 - Bowen, William R.; Warkentin, Germaine, 1933-; Black, Joseph, 1962- (University of Toronto Press, 2013)
Comprised of nearly 5000 entries, the catalogue is presented with a full introduction describing the Sidneys' intellectual world and life, their reading and collecting, the women collectors of the family, and the dispersal of the library in 1743.